Analisis Ekonomi dan Strategi Pengelolaan Ekowisata (Studi Kasus Kawasan Wisata Gunung Salak Endah Kabupaten Bogor) - Pini Wijayanti; Tanti Novianti; Hastuti Hastuti (Institut Pertanian Bogor, 2008)
Tourism has been a part of commodity that widely used by a region governmant as one of finance depelopment resources. Practicaly, the tourism development must be directed to sustainable tourism, which is one form is ecological tourism (ecotourosm).keyword: ecotourism, economic impact, environmental services Pariwisata telah menjadi bagian dari